Tabulasi genomik rangkaian massa Kampung Tambora - Husin, Denny; Komala, Olga Nauli (Program Studi Arsitektur Fakultas Teknik Universitas Katolik Widya Mandira, 2024)
Well known as one of the most crowded and problematic urban kampungs in ASEAN since 2020, Tambora has been struggle with health, fire, and social problems. Its density is related to the composition between solid and void especially on the boundary as they control the accessibility while influencing the overall gesture of the kampung. Unfortunately, the majority of research related to boundaries is more interested in delineation rather than 3D relationships. Further investigation is required to understand its series of volumetric composition, configuration, and orientation to comprehend its architecture as a continuation of its geometrical investigation. As boundaries are relatively considered more stable locations, they exhibit intensity, complexity, and hybridity between formal and informal. A diverse collection of houses at these particular locations displays specific language while providing correlation. Genomic tabulation is utilized to interpret the kampung massing series' spatial quality. The QGIS instrument converts lines into volumes, with steps are follows: 1) collection of data, 2) conversion of 2D into 3D, and 3) interpretation of the samples. By focusing on the massing series at the kampung boundaries, the typology and morphology are emerged, providing various gaps and potentials as alternative solutions for building the kampung network.